Wear behavior and XRD analysis of reinforced copper matrix composite reinforced with Cerium Oxide (CeO2). (2018) - Mishra, Tribhuwan Kishore; Kumar, Arbind; Sinha, S.K.; Gupta, Bhupendra
Abstract: In this work, tribological behavior of Copper-Cerium Oxide metal powder composite reinforced with CeO2 particles has been assessed experimentally. Four number of Cylindrical preforms with different CeO2 content (0 wt. %, 0.2 wt. %, 0.6 wt. % and 1 wt. %) at 90 KN compaction pressure have been prepared using a die and punch assembly on Universal Testing Machine by Powder Metallurgy root. Sintering at different temperatures of 900°C, 950°C and 1000°C has been carried out using Electrical Muffle Furnace (EMF). The sliding wear behavior of 12 mm diameter cylindrical sample was performed on a pin-on-disc wear tester against EN-32 steel disc (applied load 10 KN, distance 4 KM at 800 rpm) under dry ambient conditions. Finally, SEM (scanning electron microscopy) and XRD analysis has been carried out to investigate crystal grain structure and to identify the crystalline face. Densification and hardness of specimen is increased with increase of CeO2 percentage and sintering temperature. Wear decreases with increase of CeO2 content and sintering temperature when experimented. SEM and XRD test confirm uniform distribution of Cerium Oxide in copper matrix. Diffraction pattern indicates good solubility of CeO2 in copper matrix